Tcf7l1 protects the anterior neural fold from adopting the neural crest fate - Mašek, Jan; Machoň, Ondřej; Kořínek, Vladimír; Taketo, M Mark; Kozmik, Zbyněk (Development (Cambridge, England), 2016)
The neural crest (NC) is crucial for the evolutionary diversification of vertebrates. NC cells are induced at the neural plate border by the coordinated action of several signaling pathways, including Wnt/β-catenin. NC cells are normally generated in the posterior neural plate border, whereas the anterior neural fold is devoid of NC cells. Using the mouse model, we show here that active repression of Wnt/β-catenin signaling is required for maintenance of neuroepithelial identity in the anterior neural fold and for inhibition of NC induction. Conditional inactivation of Tcf7l1, a transcriptional repressor of Wnt target genes, leads to aberrant activation of Wnt/β-catenin signaling in the anterior neuroectoderm and its conversion into NC. This reduces the developing prosencephalon without affecting the anterior-posterior neural character. Thus, Tcf7l1 defines the border between the NC and the prospective forebrain via restriction of the Wnt/β-catenin signaling gradient.
Keywords: defekty neurální trubice; Prosencephalon; Humans; buněčný rodokmen; Mice, Transgenic; přední mozek; beta-katenin; Neural Tube Defects; Wnt signaling; Neural Crest; dánio pruhované; myši transgenní; Phenotype; Neural crest; lidé; Biomarkers; Mouse; zvířata; represorové proteiny; Cell Lineage; Zebrafish Proteins; Wnt Signaling Pathway; signální dráha Wnt; Forebrain; delece genu; Repressor Proteins; Gene Deletion; biologické markery; Zebrafish; protein 1 podobný transkripčnímu faktoru 7; fenotyp; integrasy; Tcf/Lef; beta Catenin; proteiny dánia pruhovaného; Animals; Transcription Factor AP-2; transdiferenciace buněk; transkripční faktor AP-2; Transcription Factor 7-Like 1 Protein; Cell Transdifferentiation; crista neuralis; Integrases